Hungarian Monitoring, 26 May 1988 . [Magyar rádiófigyelő], 1988. május 26 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - CPSU Party assembly propositions - American ratification of arms reduction agreements Domestic Affairs: - Austrian foreign minister in Budapest - Grósz welcomes president of Chinese trade unions association - Reagan statement on changes in Hungarian Party leadership - Pozsgay urges renewals in Patriotic Popular Front way of working - Opinion of churches and religious groups on Vienna follow-up talks draft document - Ministerial review of Gabčíkovo-Nagymaros on Czechoslovak territory - Situation in schools Economy: - Hungarian-Austrian links - Evaluating the Budapest International Fair - Hungarian National Bank on loans and loan policy - Trade situation Külpolitika - SZKP pártértekezlet tézisei - Fegyverkorlátozási megállapodások amerikai ratifikációja Belföld: - Budapesten az osztrák külügyminiszter - Grósz fogadja a kínai szakszervezeti szövetség elnökét - Reagan nyilatkozik a magyar pártvezetésben történt változásokról - Pozsgay a HNF munkastílusának megújítását szorgalmazza - Egyházak és felekezetek véleménye a bécsi utótalálkozó dokumentumtervezetéről - Bős - Nagymarosi miniszteri szemle a Csehszlovák területen - Iskolahelyzet Gazdaság: - Magyar-osztrák kapcsolatok - BNV értékelő - MNB a hitelfelvételről, hitelpolitikáról - Kereskedelem helyzete